TENDENSI PENDUDUK DI PAPUA MENEMPATI RUMAH BERJENIS DINDING BUKAN TEMBOK - Rafly Parenta Bano; Yashinta Irma Pratami Hematang (Musamus Journal of Architecture, 2019)
The results of Susenas (National Social Economic Survey) which conducted by BPS in 2017 show that there are stillaround 44.79 percent of households in the Papua Province that occupy uninhabitable homes. One of the criteria foruninhabitable homes is the structure of the type of wall that is of low quality (not walls). The high percentage above issuspected because the low level of population welfare is reflected in the high poverty rate in 2018 as 27.74 percent in thePapua Province. This study aims to determine the percentage of households in the Papua Province that occupy buildingswith types of walls not walls and the factors and the level of tendency. The method used is descriptive analysis andlogistic regression analysis. The results showed that there were 74.72 percent of households in the Papua Provinceoccupying buildings with types of walls not walls. Even 100 percent of households in eight districts in the Papua Provinceoccupy buildings with the same wall character. While the results of logistic regression analysis showed that the variablearea of residence, education of the head of the household and the field of business of the household head affecthouseholds occupying buildings with types not walls.